Prevalence of Antibiotic-Resistant Escherichia coli in Drinking Water Sources in Hangzhou City - Chen, Zhaojun; Yu, Daojun; He, Songzhe; Ye, Hui; Zhang, Lei; Wen, Yanping; Zhang, Wenhui; Shu, Liping; Chen, Shuchang (Frontiers in Microbiology, 2017)
This study investigated the distribution of antibiotic resistant Escherichia coli (E. coli) and examined the possible relationship between water quality parameters and antibiotic resistance from two different drinking water sources (the Qiantang River and the Dongtiao Stream) in Hangzhou city of China. E. coli isolates were tested for their susceptibility to eighteen antibiotics. Most of the isolates were resistant to tetracycline (TE), followed by ampicillin (AM), piperacillin (PIP), trimethoprim/sulfamethoxazole (SXT) and chloramphenicol (C). The antibiotic resistance rate of E. coli isolates from two water sources was similar; For E.coli isolates from the Qiantang River, their antibiotic resistance rates decreased from up- to downstream. Seasonally, the dry and wet season had little impact on antibiotic resistance. Spearman’s rank correlation revealed significant correlation between resistance to TE and phenicols or ciprofloxacin (CIP), as well as quinolones (ciprofloxacin and levofloxacin) and cephalosporins or gentamicin (GM). Pearson’s chi-square tests found certain water parameters such as nutrient concentration were strongly associated with resistance to some of the antibiotics. In addition, tet genes were detected from all 82 TE-resistant E. coli isolates, and most of the isolates (81.87%) contained multiple tet genes, which displayed 14 different combinations. Collectively, this study provided baseline data on antibiotic resistance of drinking water sources in Hangzhou city, which indicates drinking water sources could be the reservoir of antibiotic resistance, potentially presenting a public health risk.